PNEUMONIA CASES AMONG TODDLERS BASED ON EXCLUSIVE BREASTFEEDING COVERAGE, UNDERNUTRITION STATUS, AND POPULATION DENSITY IN SIDOARJO REGENCY IN 2019, 2020, AND 2021 - Wigunawanti, Rezandra Anggita; Astutik, Erni; Khan, Rukhsana (Universitas Airlangga, 2024)
Introduction: Pneumonia is the leading infectious cause of death among children worldwide accounting for 14% of all under-five deaths. Sidoarjo Regency has the highest incidence of toddlers with pneumonia in East Java. Aims: This study aimed to map and analyze the distribution of pneumonia cases among toddlers in the Sidoarjo Regency based on the risk factors of exclusive breastfeeding coverage, lack of nutrition status, and population density. Methods: This research was a descriptive study using secondary data obtained from the Sidoarjo Regency Health Profile in 2019, 2020, and 2021. This study’s analysis unit included all 18 sub-districts in Sidoarjo Regency. Mapping was done using QGIS software version 3.10, “A Coruña.” Results: The findings showed that the Waru Sub-district was vulnerable to the incidence of pneumonia in toddlers because, apart from consistently having a high prevalence of cases over the last three years, it was also accompanied by high-risk factors, including low coverage of exclusive breastfeeding, high incidence of undernourished toddlers, and high population density. Conclusions: It can be concluded that intervention activities such as socializing and advocating programs of exclusive breastfeeding and balanced toddler nutrition with PMT and immunization are better prioritized in Waru Sub-district.